Hospital Bylaws Hospitals in Providing Legal Protection Against Criminal Acts of Medical Personnel - Yongky Yongky; Kiki Kristanto; Satriya Nugraha (Green Publisher Indonesia, 2025)
Hospitals have a strategic role in providing comprehensive health services and ensuring legal protection for medical personnel in carrying out their professional practices. The existence of Hospital Bylaws or internal hospital regulations is an important instrument in creating good hospital governance and providing legal protection for medical personnel against possible lawsuits due to alleged negligence or malpractice. This study examines the role of Hospital Bylaws in providing legal protection for medical personnel with a legislative and conceptual approach. The results of the study show that Hospital Bylaws have a role in setting ethical and professional standards, dispute resolution mechanisms, and legal responsibilities of hospitals and medical personnel. Therefore, the optimal implementation of Hospital Bylaws can be a preventive effort in reducing potential medical disputes and improving the quality of health services in hospitals.